1994
DOI: 10.1115/1.2929570
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Effects on a Large Piping System During Strong Earthquakes

Abstract: Liquid in a large piping system could become a resonance column under axial excitations. A 1000-m long closed-boundaries pipeline with pressure wave propagation velocity of 1000 m/s would have the fundamental liquid resonance frequency of 0.5 Hz. Then, some hydraulic transients might occur during strong earthquakes. If dynamic pressure amplitude exceeds the value of system stationary pressure, then vaporizing at negative pressure, and after that, cavity or liquid column separation and reconnection can be produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The problem with this approach is the long time required to sweep through each frequency, as each frequency requires that the system settle down to steady oscillatory conditions. In addition, the excitation of a pipeline at the resonance frequencies can also inflict substantial damage to the system (Ogawa et al, 1994).…”
Section: Generation Of the Frd Under Realistic Situationsmentioning
confidence: 99%
“…The problem with this approach is the long time required to sweep through each frequency, as each frequency requires that the system settle down to steady oscillatory conditions. In addition, the excitation of a pipeline at the resonance frequencies can also inflict substantial damage to the system (Ogawa et al, 1994).…”
Section: Generation Of the Frd Under Realistic Situationsmentioning
confidence: 99%
“…Ogawa et al [73] applied an analytical model of earthquake-induced fluid transients to an inplace underground piping network. Using an artificially modified earthquake for excitation 33 combined with frequency-domain analysis, they concluded that induced sub-atmospheric pressures in the liquid were possible, and demonstrated how two parallel pipes in the same network could have one fail axially while the other experienced no damage, because of the different waterhammer response in each pipe.…”
Section: Earthquake Engineeringmentioning
confidence: 99%
“…In Ogawa [1980]; Ogawa et al [1994], system matrix transfer functions for pressure and velocity sinusoidal amplitude distributions were derived for arbitrary networks. In this work, spatial earthquake vibrations were the transient state driver for the system, and as such, the fluid line equations incorporated axial displacement terms.…”
Section: Current Methods For Modeling Arbitrary Networkmentioning
confidence: 99%
“…In this work, spatial earthquake vibrations were the transient state driver for the system, and as such, the fluid line equations incorporated axial displacement terms. Ogawa [1980]; Ogawa et al [1994] reduce their model to a set of two unknowns for each pipe (one coefficient for each pipe's positive and negative traveling waves).…”
Section: Current Methods For Modeling Arbitrary Networkmentioning
confidence: 99%